2001
DOI: 10.1007/s002340000477
|View full text |Cite
|
Sign up to set email alerts
|

MRI and CT of adenomatous tumours of the middle ear

Abstract: We report three adenomatous middle-ear tumours, an adenoma, an adenocarcinoma and a semimalignant adenomatous tumour, with special attention to CT and MRI findings. In all cases we found small intratympanic masses in which the ossicles were embedded. All showed contrast enhancement and similar signal intensity as brain tissue on T1- and T2-weighted images. The biological nature of the tumours was not reflected by the imaging or operative findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 0 publications
0
6
0
12
Order By: Relevance
“…The ossicles are generally embedded in the mass without ossicular or bony erosion. No characteristic differences between the benign and malignant tumors are detectable on a CT [13]. On an MRI, the tumors are isointense or generated a slightly higher signal than white matter on T1-weighted images; there is contrast enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ossicles are generally embedded in the mass without ossicular or bony erosion. No characteristic differences between the benign and malignant tumors are detectable on a CT [13]. On an MRI, the tumors are isointense or generated a slightly higher signal than white matter on T1-weighted images; there is contrast enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…On an MRI, the tumors are isointense or generated a slightly higher signal than white matter on T1-weighted images; there is contrast enhancement. On T2-weighted images, the tumors approximate the signal intensity of gray matter [13]. Although the ossicles are visible as signal voids within the tumor, bone erosion could not be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of our patient showed irregular soft tissue lesion in the inner part of left auditory canal just lateral to the tympanic membrane without any bony erosive change. Earlier radiological studies on NAME some patients have showed homogenous, hypodense lesions of temporal bone well limited to the middle ears [8, 12]. The patient in this study underwent a complete excision of the left middle ear tumor along with radical mastoidectomy to avoid future recurrence.…”
Section: Discussionmentioning
confidence: 85%
“…No tienen predominancia de sexo (1)(2)(3)(4) y la edad de aparición puede variar entre los 7 hasta los 80 años (4) . La presentación clínica es inespecífica (5) . El síntoma más común es la hipoacusia unilateral de meses a años de evolución (4,5) .…”
Section: Introductionunclassified
“…La presentación clínica es inespecífica (5) . El síntoma más común es la hipoacusia unilateral de meses a años de evolución (4,5) . Otros síntomas incluyen sensación de plenitud en el oído (1,5) y tinnitus (1,4,5) .…”
Section: Introductionunclassified